New religious movements in North America: an introduction - Willsky-Ciollo, Lydia (Bloomsbury religion in North America, 2024)
"Among the new religious movements explored in this book are the Church of Scientology, the Branch Davidians, the Nation of Islam, the Church of Jesus Christ of Latter-day Saints. Topics covered include yoga, contemporary wellness and spirituality, the American Atheist, Environmentalism, Covid-19, and the anti-cult movement in America. All of these examples are explored with an eye to answering not only "what new religious movements are" but why it is important to learn and talk about new religious movements. Illustrated throughout with over 75 images, each chapter finishes with guidance on further reading"--